2000
DOI: 10.1038/sj.jhh.1001012
|View full text |Cite
|
Sign up to set email alerts
|

Working under pressure: the vascular endothelium in arterial hypertension

Abstract: The vascular endothelium synthesizes and releases a spectrum of vasoactive substances like nitric oxide (NO) and endothelin (ET). In hypertension, the delicate balance of endothelium-derived factors is disturbed. ET acts as the natural counterpart to endothelium-derived NO, which exerts vasodilating, antithrombotic, and antiproliferative effects, and inhibits leukocyte-adhesion to the vascular wall. Besides its blood pressure rising effect also in man, ET induces vascular and myocardial hypertrophy, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 191 publications
2
33
0
Order By: Relevance
“…Thus, it is possible that the increased TM/Cr ratio reflects endothelial damage in hypertensive patients. In fact, endothelium-dependent relaxations have shown to be impaired in hypertensive animals and in humans with essential hypertension (13)(14)(15). However, it has been reported that circulating TM levels were not related to an endothelium-dependent increase in forearm blood flow induced by acetylcholine in patients with hypercholesterolaemia (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that the increased TM/Cr ratio reflects endothelial damage in hypertensive patients. In fact, endothelium-dependent relaxations have shown to be impaired in hypertensive animals and in humans with essential hypertension (13)(14)(15). However, it has been reported that circulating TM levels were not related to an endothelium-dependent increase in forearm blood flow induced by acetylcholine in patients with hypercholesterolaemia (24).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function is impaired in hypertension (13)(14)(15), and this plays a crucial role in the initial development of atherosclerosis (16). This raises the question of whether soluble TM is elevated in patients with hypertension in proportion to the progression of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms of OSA-induced reduction of nitric oxide include: (1) superoxidemediated scavenging of nitric oxide, generating products such as peroxynitrite which can nitrosylate membrane proteins and oxidize lipids [49]; (2) reduction of molecular oxygen, which serves as a cosubstrate for nitric oxide synthesis; (3) increased NOS inhibitors; and (4) suppression of endothelial NOS expression [50]. Two of these hypotheses have been directly addressed in studies of human OSA patients.…”
Section: Evidence For Altered Nitric Oxide Production In Osa Patientsmentioning
confidence: 99%
“…O 22 reacts with nitric oxide (NO), an endothelium-derived relaxing factor, to form peroxynitrite (ONOO 2 ). Thus, under conditions of excess O 22 production, such as hypertension, increased oxidative stress and reduced bioavailability of NO impair endothelial function, leading to the progression of hypertension (16,17). NADPH oxidase is the main generator of reactive oxygen species in the vasculature (18), while reactive oxygen species promote further activation of NADPH oxidase in a feed-forward mechanism (19).…”
Section: 1% Ghesmentioning
confidence: 99%